KEEFEKTIVAN PENGGUNAAN METODE THINK TALK WRITE DALAM PEMBELAJARAN MENULIS TEKS ULASAN PADA SISWA MTS - Irna Rosdiana; Ijang Subarna; Tamtam Kamaludin (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is based on the curiosity of researchers in the use of think talk write method towards review text learning in class VIII Mts Asaasuttarbiyah Mande. From the research background, researchers can draw a problem statement, namely Is the think talk write method effectively used in learning to write review texts? and thus the researcher aims to determine the ability to write review texts on class VIII Mts Asaasuttarbiyah this study also intends to determine the effectiveness of the think talk write method in learning to write review texts. Review texts are chosen because they can help students train students in the language fluently and develop student writing. The method that the researcher uses is the experimental method. In this study, the researchers used one group design pretest-posttest. Data taken by researchers is quantitative data, namely data analyzed by passing statistical analysis techniques. The class that the researcher chooses is class VIII A with 30 students being sampled for the research material. For this reason the results of the study state that the initial test (pretest) and the final test (posttest) change or increase with the results of the initial test 63 and the final test average 81 results. For this reason, the researcher can conclude that the writers' talk method is effective (influential) to be used in learning to write review texts.